Legal Protection Against Workers which is Terminated by Entrepreneurs without any Agreement - Arly, Ibnu; Aulia, Medina Citra (Budapest International Research and Critics University, 2021)
Legal protection is an act to protect legal subjects with applicable laws and regulations and their implementation can be enforced with a sanction. Workers are workers who work in an employment relationship with employers by receiving wages [1]. Meanwhile, according to Law Number 13 of 2003 concerning Manpower Article 1 number 3, a worker is anyone who works by receiving wages or other forms of remuneration. Termination of Employment Relationship is the termination of the employment relationship due to a certain matter which results in the termination of the rights and obligations between the worker and the entrepreneur. An employment agreement is an agreement between a worker and an entrepreneur or employer that contains the terms of employment, rights and obligations of the parties. In Law No. 13 of 2003, the work agreement is divided into two, namely: 1. Work Agreement for a certain period of time; 2. Indefinite Time Employment Agreement. In Article 1601a of the Civil Code (BW) it is stated that a labor agreement is an agreement in which the first party, the worker, binds under the leadership of another party, the employer for a certain time, to do work by receiving wages.